STEM FROM HOME: THE TRAINING FOR PRIMARY SCHOOL TEACHERS IN BANDUNG WETAN AS A SCIENCE LEARNING ALTERNATIVE DURING THE COVID-19 PANDEMIC - Dede Trie Kurniawan; Yeni Yuniarti; Rendi Restiana Sukardi; Novi Yanthi; Hana Yunansah; Sri Maryanti (LPM Universitas Pasundan, 2020)
This Community Service Program aims to increase the ability of elementary school teachers in Bandung Wetan district to develop STEM-based science learning plans during the Covid-19 pandemic. In detail, the objectives of this service can be described as follows: first knowing the teacher's perceptions of the implementation of STEM learning that is carried out in online learning, second knowing the teacher's needs for the implementation of STEM in online learning, the third design of the SFH training program (STEM From Home ) to improve the ability of elementary school teachers in Bandung Wetan sub-district to develop a STEM-based science learning plan during the Covid-19 pandemic and most recently as an effort to describe the ability of elementary school teachers in Bandung Wetan sub-district to develop a STEM-based science learning plan during the Covid-19 pandemic after participating in the program SFH (STEM From Home) training. This service activity targets the target audience is elementary school teachers in the Bandung Wetan district. The number of schools in Bandung Wetan District is 17 with 15 private schools and 2 public elementary schools. On this occasion, the involvement of teachers as many as 28 people was prioritized. A series of PKM activities have been carried out from August to September 2020. And Broadly speaking, the participants of the activities gave positive responses to the implementation of In House Training activities: SFH (STEM From Home) Implementation Strategies as Alternative Learning Ipa During the Covid-19 Pandemic Period for Teachers Bandung Wetan elementary school